Synergistic Effects of Double Cation Substitution in Solution‐Processed CZTS Solar Cells with over 10% Efficiency. Issue 32 (4th October 2018) - Hadke, Shreyash H.; Levcenko, Sergiu; Lie, Stener; Hages, Charles J.; Márquez, José A.; Unold, Thomas; Wong, Lydia H.
Abstract: The performance of many emerging compound semiconductors for thin‐film solar cells is considerably lower than the Shockley–Queisser limit, and one of the main reasons for this is the presence of various deleterious defects. A partial or complete substitution of the cations presents a viable strategy to alter the characteristics of the detrimental defects and defect clusters. Particularly, it is hypothesized that double cation substitution could be a feasible strategy to mitigate the negative effects of different types of defects. In this study, the effects of double cation substitution on pure‐sulfide Cu2 ZnSnS4 (CZTS) by partially substituting Cu with Ag, and Zn with Cd are explored. A 10.1% total‐area power conversion efficiency (10.8% active‐area efficiency) is achieved. The role of Cd, Ag, and Cd + Ag substitution is probed using temperature‐dependent photoluminescence, time‐resolved photoluminescence, current–voltage ( IV ), and external quantum efficiency (EQE) measurements. It is found that Cd improves the photovoltaic performance by altering the defect characteristics of acceptor states near the valence band, and Ag reduces nonradiative bulk recombination. It is believed that the double cation substitution approach can also be extended to other emerging photovoltaic materials, where defects are the main culprits for low performance. Abstract : Double cation substitution in Cu2 ZnSnS4 (CZTS) by partially substituting Cu with Ag and Zn with Cd is shown to alter the characteristics of acceptor defects and deep defects responsible for non‐radiative recombination. This synergistic effect of Cd and Ag reflects in power conversion efficiency of 10.1% (10.8% active area) obtained in the (Cu, Ag)2 (Zn, Cd)SnS4 system.